HUBUNGAN CITRA TUBUH, AKTIVITAS FISIK, KEBIASAAN MAKAN DAN PENGETAHUAN GIZI SEIMBANG TERHADAP STATUS GIZI MAHASISWA FAKULTAS ILMU KESEHATAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2022 - Delfianny Octausgoraputry (2022)
The quality of adolescents can be seen from the adequacy of nutritional intake from an early age. Factors that affect nutritional status are age, gender, body image, physical activity, eating habits, and knowledge. This study aims to determine the relationship between body image, physical activity, eating habits, and knowledge of balanced nutrition on nutritional status and body image with gender in students of the Faculty of Health Sciences, National Veterans Development University, Jakarta. This study used a cross-sectional study that required 92 samples. The sampling technique used stratified random sampling. Bivariate analysis using chi square test and spearman rank test. Based on the results, it can be concluded that there is a relationship between body image and nutritional status, but there is no relationship between physical activity, eating habits, and knowledge of nutrition with nutritional status and there is also no relationship between body image and gender. This study suggests respondents to pay more attention to their weight and can apply a healthy lifestyle according to the required recommendations. Institutions can make programs or socialization related to the importance of nutritional status, increase physical activity, and consume balanced nutritious foods to increase respondents' knowledge.